Health information : management of a strategic resource - Abdelhalim (St. Louis, Mo. : Saunders/Elsevier, 2007)
Gives prospective health information management professionals the knowledge, confidence, and practical application experience to succeed in health informatics
Includes bibliographical references and index
10 13
Keywords: Information resources management; Medical Informatics